LEGISLATION OF THE REPUBLIC OF UZBEKISTAN REGULATING THE FIELD OF INTERNET SECURITY (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
While the article applauds the legislative initiatives implemented in Uzbekistan, it also raises important points of concern. It mentions the challenges of keeping the legislation up to date with rapidly evolving technologies and the need for continuous monitoring and revision. Additionally, the article calls for increased awareness and education about internet security among citizens to fully realize the benefits of the legal framework.